Integrating UPLC-Q-Orbitrap MS with serum pharmacochemistry network and experimental verification to explore the pharmacological mechanisms of Cynanchi stauntonii rhizoma et radix against sepsis-induced acute lung injury - Gao, Hejun; Yuan, Ziyi; Liang, Haoxuan; Liu, Youtan (Frontiers in Pharmacology, 2024)
Patients with sepsis are at an incremental risk of acute lung injury (ALI). Baiqian, also known as Cynanchum stauntonii (Decne.) Schltr. ex Lé vl. (Csrer), has antiinflammatory properties and is traditionally used to treat cough and phlegm. This study aimed to demonstrate the multicomponent, multitarget, and multi-pathway regulatory molecular mechanisms of Csrer in treating lipopolysaccharide (LPS)induced ALI. The bioactive components of Csrer were identified by ultrahighperformance liquid chromatography Q-Orbitrap mass spectrometry (UPLC-Q-Orbitrap MS). Active targets predicted from PharmMapper. DrugBank, OMIM, TTD, and GeneCards were used to identify potential targets related to ALI. Intersection genes were identified for Csrer against ALI. The PPI network was analysed to identify prime targets. GO and KEGG analyses were performed. A drug-compound-targetpathway-disease network was constructed. Molecular docking and simulations evaluated the binding free energy between key proteins and active compounds. The protective effect and mechanism of Csrer in ALI were verified using an ALI model in mice. WB, RT-PCR, and immunofluorescence evaluated the mechanisms of the pulmonary protective effects of Csrer. Forty-six bioactive components, one hundred and ninety-two potential cross-targets against ALI and 10 core genes were identified.According to GO and KEGG analyses, the PI3K-Akt, apoptosis and p53 pathways are predominantly involved in the "Csrer-ALI" network. According to molecular docking and dynamics simulations, 10 key genes were firmly bound by the principal active components of Csrer. The "Csrer-ALI" network was revealed to be mediated by the p53-mediated apoptosis and inflammatory pathways in animal experiments. In conclusion, Csrer is a reliable source for ALI treatment based on its practical components, potential targets and pathways.